Staring down the tiger : stories of Hmong American women - Vang, Pa Der, 1975- (Minnesota Historical Society Press, 2020)
Hmong American women reclaim the phrase tsov tom or "tiger bite," showing in prose and poetry that they are strong enough and brave enough to stare down the tiger. Contributors celebrate the power of bonds between daughter and mother, sister and sister and grandmother and granddaughter. These writers bring life and character to the challenges of maintaining identity, navigating changes in gender roles, transitioning to American culture and breaking through cultural barriers.